웹소설 플랫폼을 사용한 창작 동화 교육의 학생 수용과 만족도 - 김기호(Ki-Ho Kim); 안의진(Ui-Jin Ahn) (교양교육연구, 2025)
본 연구는 아날로그 창작 동화 텍스트를 디지털 웹으로 문서화 하여 플랫폼에 업로드를 하는 아날로그의 디지털 전환교육이 학생들에게 어떻게 수용되고 어떠한 정서적 만족감을 주는지 알아보고자 했다. 그리고 유용도와 만족도가 미래 디지털 도구의 사용에 어떻게 반응하는지도 확인하고자 했다. 연구 결과를 요약해서 제시하면 다음과 같다. 첫째 ‘유용도’의 면에서 학생들은 웹소설 플랫폼의 사용 가치(4.0/5)를 높게 평가하는 것으로 나타났다. 둘째 ‘만족도’의 면에서도 학생들은 웹소설 플랫폼의 심리적 충족감(3.9/5)을 높게 표현하였다. 셋째 ‘유용도’와 앞으로의 ‘사용의도’의 관계, 그리고 ‘만족도’와 앞으로의 ‘사용의도’의 관계를 살핀 결과 ‘유용도’와 ‘사용의도’ 사이의 관계는 유의미하였다. 그러나 ‘만족도’와 ‘사용의도’ 사이의 관계는 유의도가 낮았다. 학생들은 플랫폼의 유용성을 인식하는 것을 원인으로 하여 미래에도 결과적으로 플랫폼을 계속 사용하겠다는 의지를 유의미하게 나타냈다. 그러나 플랫폼 사용에 따른 만족을 원인으로 하여 미래에도 결과적으로 플랫폼을 계속 사용하겠다는 의지는 의미 있게 보이지 않았다. 마지막으로 창작 동화의 플랫폼 게시 활동에서 플랫폼과 웹의 장점을 계속 수용하기 위해서는 학생들이 플랫폼과 웹에 대해 갖는 심리적 부담감을 완화할 필요가 있다는 것이 확인되었다. 부담감은 ‘자기 글 공개에 대한 거부감’, ‘부정적 댓글에 대한 두려움’, ‘공개되는 만큼 완벽해야 한다는 부담감’ 등이다. 이들 부담감은 모두 심리적인 요인이다. 그러므로 창작 동화 교육에서 플랫폼과 웹의 장점을 지속적으로 활용하기 위해서는 심리적 부담을 완화하는 웹(Web) 사용성 교육이 포함되어야 한다는 사실이 확인되었다. This study aims to investigate how transformation education from analog to digital, which documents creative children's stories in analog formats into digital web and uploads them on a platform, is accepted by students and satisfies them emotionally. The study also sets out to examine how their acceptance and satisfaction react to the use of digital tools in the future. The findings are summarized as follows: first, students gave a high rating to the use value(4/5) of a web novel platform in the aspect of “utility”; second, they showed a high level of psychological satisfaction(3.9/5) with a web novel platform in the aspect of “satisfaction”; third, the study examined relations between “utility” and “intention for future use” and between “satisfaction” and “intention for future use” and found significant relations between “utility” and “intention for use” and no significant relations between “satisfaction” and “intention for use.” Students recognized the utility of a platform, thus showing their willingness to keep using a platform in the future. However, they had no willingness to keep using a platform in the future for their satisfaction with using one; and finally, there was a need to mitigate students' psychological resistance to a platform and web so that they would continue to accept the advantages of a platform and web in the activity of uploading their creative children's stories on a platform. Resistance includes “rejection to making public their stories,” “fear for negative comments,” and “burden with writing perfect stories to make public them.” All of such resistance is psychological, which raises a new fact that these psychological resistance factors should be alleviated for the continuous use of a platform and web in education on creative children's stories. KCI Citation Count: 0